2020
DOI: 10.1038/s41380-020-00972-4
|View full text |Cite
|
Sign up to set email alerts
|

ZFP804A mutant mice display sex-dependent schizophrenia-like behaviors

Abstract: Genome-wide association studies uncovered the association of ZNF804A (Zinc-finger protein 804A) with schizophrenia (SZ). In vitro data have indicated that ZNF804A might exert its biological roles by regulating spine and neurite morphogenesis. However, no in vivo data are available for the role of ZNF804A in psychiatric disorders in general, SZ in particular. We generated ZFP804A mutant mice, and they showed deficits in contextual fear and spatial memory. We also observed the sensorimotor gating impairment, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Female ZFP804A mutant mice show age-dependent defects in sensorimotor gating. Thinking disorder and distraction occurred only after 6 months of age, while the damage to spatial and fear memory was obvious when they were young [ 201 ]. Researchers also found that the deletion of ZFP804A had an impact on the language, reading, and cognitive abilities of the population.…”
Section: Zfp and The Cellular Pathwaysmentioning
confidence: 99%
“…Female ZFP804A mutant mice show age-dependent defects in sensorimotor gating. Thinking disorder and distraction occurred only after 6 months of age, while the damage to spatial and fear memory was obvious when they were young [ 201 ]. Researchers also found that the deletion of ZFP804A had an impact on the language, reading, and cognitive abilities of the population.…”
Section: Zfp and The Cellular Pathwaysmentioning
confidence: 99%
“…This latter point is important because there is evidence from animal studies that estradiol exerts a substantial effect on cognition [ 41 , 42 , 43 , 44 ]. Preclinical studies have shown, for instance, that mutant mice display sex-dependent schizophrenia-like behaviors in animal models [ 45 ]. Male rats in animal models show significantly more severe cognitive dysfunction than female rats [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following the discovery of this gene, researches using model organisms to examine the biological functions of DISC1 have achieved fruitful results. There are three main types of Disc1 mouse models of schizophrenia: haploinsufficient dose model, point mutation model and transgenic model (Tomoda, Sumitomo, Jaaro‐Peled, & Sawa, 2016), as outlined in Table 3 (Arguello & Gogos, 2010; Babovic et al, 2007; Bhardwaj, Ryan, et al, 2015; Brown et al, 2011; Brzozka & Rossner, 2013; Clapcote et al, 2007; Gandal et al, 2012; Glen Jr. et al, 2014; Guo et al, 2009; Hikida et al, 2007; Huang et al, 2014; Huang et al, 2020; Koike et al, 2006; Kuroda et al, 2011; Lee et al, 2013; Li, Zhou, et al, 2007; Lipina et al, 2010; Olaya et al, 2018; Ortega‐Alvaro et al, 2011; Papaleo et al, 2016; Pei et al, 2014; Petit et al, 2017; Pletnikov et al, 2008; Shoji et al, 2012; Sobue et al, 2018; Su et al, 2014; Zhang et al, 2015).…”
Section: Genetically Engineered Animal Experimental Modelsmentioning
confidence: 99%
“…Long‐term depression was only facilitated in female mutant mice. The results suggested that ZNF804A plays an important role in the cognitive functions and sensorimotor gating, particularly in the female patients (Huang et al, 2020).…”
Section: Genetically Engineered Animal Experimental Modelsmentioning
confidence: 99%